Evaluation of the effect of cooking methods on vitamin C content in broccoli - Nunes, M. (2020)
Introduction: Vitamin C is a water-soluble vitamin necessary for the synthesis of collagen and muscle carnitine, absorption of iron from non-heme iron sources, among others (1). Fruits and vegetables naturally contain high levels of vitamin C (2). The oxidation of L-ascorbic acid in dehydroascorbic acid is common in the presence of oxygen, light, temperature, high pressures, and alkaline pH (3). In this study, the influence of different cooking methods on the total vitamin C, L-ascorbic and dehydroascorbic acids contents in broccoli (Brassica oleracea L. var. italica) was evaluated. Materials and Methods: In 2019, the broccoli were purchased from commercial stores in Lisbon region. The samples were manually separated between edible portion and non-edible portion. The broccoli were analyzed raw and after being submitted to 6 cooking methods (boiled, steamed, cooked in the microwave, purée, sautéed with garlic and olive oil and gratin with béchamel sauce and cheese in an oven). Separation and quantification of vitamin C was carried out on an Alliance 2695 HPLC system, with diode array detection. Samples were monitored at 245 nm (4). Results: Raw broccoli presented 93.4 ± 8.6 mg/100 g of total vitamin C, 58.6 ± 1.6 mg/100 g of L-ascorbic acid and 34.8 ± 7.1 mg/100 g of dehydroascorbic acid. Steamed broccoli was the sample with the highest total vitamin C, L-ascorbic and dehydroascorbic acids contents (89.3 ± 0.7 mg/100 g, 77.8 ± 1.5 mg/100 g and 11.6 ± 1.5 mg/100 g, respectively). The gratin of broccoli was the sample with the lowest total vitamin C content, 24.3 ± 0.5 mg/100 g. Discussion and conclusions: The results reported wherein allow concluding that cooking methods applied to foods affect the stability of the bioactive compounds, such as vitamin C. Thereof, it is of utmost importance to evaluate different cooking methods and to determine which are more suitable to preserve the content of the promoting health components of food.